Synergy Between Vitamin D and Sex Hormones in Respiratory Functionality of Patients Affected by COVID-19 - Peruzzu, Daniela; Pagano, Maria Teresa; Pierdominici, Marina; Ruggieri, Anna; Antinori, Andrea; D’Offizi, Gianpiero; Petrosillo, Nicola; Palmieri, Fabrizio; Piselli, Pierluca; Boumis, Evangelo; Notari, Stefania; Nicastri, Emanuele; et al. (Frontiers in Pharmacology, 2021)
The outcome of COVID-19 appears to be influenced by vitamin D status of population. Although epidemiological data indicate that COVID-19 produces more severe symptoms and higher mortality in elderly in comparison to young patients and in men in comparison to women to date sex and age differences in vitamin D status in infected patients have not been evaluated yet. In this study we evaluated the levels of circulating 25(OH)D in patients hospitalized for COVID-19 divided accordingly to their sex and age. We also correlated 25(OH)D levels with patient’s respiratory status (i.e., PaO2/FiO2 ratio) and with sex hormones plasma levels to analyze the potential relationship of these parameters. We found no significant differences in plasma levels of 25(OH)D between pre- and post-menopausal female patients and age matched male patients. Interestingly, the 25(OH)D plasma levels positively correlated to PaO2/FiO2 ratio only in young patients, regardless of their sex. We also found a significantly positive correlation between 17β-estradiol and 25(OH)D in elderly women and between testosterone and 25(OH)D in elderly men, supporting the role of sex hormones in maintaining 25(OH)D levels. In conclusion, we suggest that a synergy between vitamin D and sex hormones could contribute to the age-related outcome of COVID-19.